SOSIALISASI PENINGKATAN POTENSI EKOWISATA PULAU DEPI’ SEBAGAI SENTRA WISATA DI DESA LABUHAN BONTONG KECAMATAN TARANO SUMBAWA - Wahyu Indah Widya Astuti; Kamarullah Hansani; Susilawati; Acica Luandari; Wahidah Priscillah; Ory Auliyah; Ika Citra Dewi Adekayanti; Lahmianti; Sri Wahyuni; Erlin Exayanti Putri; Nauval Akbar; Ardiansyah; Hermansyah (FKIP Universitas Samawa, 2021)
Labuhan Bontong Village is one of the villages located in Tarano District, Sumbawa. This village has a lot of potentials that has not been developed, one of which is the potential of the island of Depi' which can be used as an ecotourism center. The purpose of this activity is to increase public awareness of the potential possessed by the village in order to increase village income and to increase public awareness of environmental conservation. This activity was carried out in Labuhan Bontong Village, Tarano District, Sumbawa Regency, West Nusa Tenggara. The implementation method used consists of three stages, namely the preparation, implementation, and evaluation stages. The results obtained from this activity are in the form of a positive and enthusiastic response from the Village apparatus and residents and villagers through the village head of Labuhan Bontong hoping that this activity can increase community income in the future.